Coordination of Drosophila metamorphosis by two ecdysone-induced nuclear receptors. - White, K.P.; Hurban, P.; Watanabe, T.; Hogness, D.S. (Science, 1997)
The functions of the ecdysone-induced DHR3 and E75B orphan nuclear receptors in the early stages of Drosophila metamorphosis were investigated. DHR3 represses the ecdysone induction of early genes turned on by the pulse of ecdysone that triggers metamorphosis. It also induces betaFTZF1, an orphan nuclear receptor that is essential for the appropriate response to the subsequent prepupal pulse of ecdysone. The E75B receptor, which lacks a complete DNA binding domain, inhibits this inductive function by forming a complex with DHR3 on the betaFTZF1 promoter, thereby providing a timing mechanism for betaFTZF1 induction that is dependent on the disappearance of E75B.